Study on preparation, characterization and multidrug resistance reversal of red blood cell membrane-camouflaged tetrandrine-loaded PLGA nanoparticles - Xiao Que; Jing Su; Pengcheng Guo; Zul Kamal; Enge Xu; Siyu Liu; Jieyu Chen; Mingfeng Qiu (Taylor & Francis Group, 2019)
The multidrug resistance in tumor (MDR) is a major barrier to efficient cancer therapy. Modern pharmacological studies have proven that tetrandrine (TET) has great potential in reversing MDR. However, it has a series of medication problems in clinic such as poor water solubility, low oral bioavailability and short half-life in vivo. Aiming at the above problems, red blood cell membrane-camouflaged TET-loaded poly(lactic-co-glycolic acid) (PLGA) nanoparticles (RPTNs) had been developed. The RPTNs had spherical shell-core double layer structure with average particle size of 164.1 ± 1.65 nm and encapsulation efficiency of 84.1% ± 0.41%. Compared with TET-PLGA nanoparticles (PTNs), the RPTNs reduced RAW 264.7 macrophages' swallowing by 32% due to its retention of natural membrane proteins. The cumulative drug release of RPTNs was 81.88% within 120 h. And pharmacokinetic study showed that the blood half-life of RPTNs was 19.38 h, which was 2.95 times of free drug. When RPTNs of 2 μg/mL TET were administered in combination with adriamycin (ADR), significant MDR reversal effect was observed in drug-resistant cells MCF-7/ADR. In a word, the RPTNs hold potential to improve its efficacy and broaden its clinical application.